Effect of sacralization on the success of lumbar transforaminal epidural steroid injection treatment: prospective clinical trial - ŞENCAN, SAVAŞ; BİLİM, SERHAD; GÜNDÜZ, OSMAN HAKAN (My University, 2022)
Objective The aim of this study was to invastigate the efect of the sacralization on the results of transforaminal epidural steroid injection for radicular low back pain. Materials and methods The study included 64 patients diagnosed with radicular low back pain due to unilateral and singlelevel lumbar disk herniation. Patients were divided into 2 groups: patients with sacralization (Group S) and patients without lumbosacral transitional vertebrae (Group A). Injection was applied to the relevant level. Patients were evaluated with Numeric Rating Scale and Modifed Oswestry Disability Index before, at week 3 and month 3 after the procedure. Sacralization presence was determined by MRI. Sacralization was categorized by anteroposterior lumbar radiography using Castellvi classifcation. Treatment success was considered as≥50% reduction in NRS scores. Results Numeric Rating Scale and Modifed Oswestry Disability Index scores decreased in both groups on both week 3 and month 3 (p<0.05). Pain scores of Group S (median value 5 (3–6)) were signifcantly higher than Group A ((median value 3 (0–5)) in the third month follow-up (p=0.026), but no signifcant diference was observed at other time points. There was no signifcant diference in Modifed Oswestry Disability Index scores between the groups at all follow-ups (p>0.05). Treatment success in the third month was 44.8% in Group S and 65.6% in Group A. Conclusion Transforaminal epidural steroid injection is an efective and safe method for radicular low back pain. Sacralization presence should be evaluated before treatment considering that it may be a risk factor reducing treatment success.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nükleer Tıp; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Nuclear medicine; Surgery Medicine Sciences; Orthopedics and Traumatology; ORTOPEDİ; Klinik Tıp; Klinik Tıp (MED); RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; ORTHOPEDICS; CLINICAL MEDICINE; Clinical Medicine (MED); RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Ortopedi ve Spor Hekimliği; Radyoloji, Nükleer Tıp ve Görüntüleme; Radyoloji ve Ultrason Teknolojisi; Ayak Bakımı; Orthopedics and Sports Medicine; Radiology, Nuclear Medicine and Imaging; Radiological and Ultrasound Technology; Podiatry; Lumbar radicular pain; Low back pain; Transforaminal epidural steroid injection; Sacralization; Lumbosacral transitional vertebrae; LUMBOSACRAL TRANSITIONAL VERTEBRAE; LOW-BACK-PAIN; RADICULAR PAIN; DOUBLE-BLIND; DEGENERATION; PREVALENCE; HERNIATION; Lumbar radicular pain · Low back pain · Transforaminal epidural steroid injection · Sacralization · Lumbosacral transitional vertebrae